THE MAIN ROLES OF PERCEPTION IN COGNITIVE PROCESSES - Huseynli Chinara Aydin (Interdisciplinary Science Studies, 2025)
Perception is one of the main psychological processes in human understanding of the world around us. In psychology, perception is explained as the transformation of information received through the sensory organs into whole, meaningful images in the brain. This process is not just the accumulation of sensations, but a complex cognitive activity that is closely related to a person’s previous knowledge, experience, emotional state and attention. Perception is a fundamental factor that determines human behavior, decision-making, orientation in everyday life and communication with the environment. The study of perception is of great importance in psychology, because how a person sees the world, how he recognizes objects and how he analyzes events shapes his way of thinking. Without perception, other cognitive processes of human activity - thinking, memory, attention - cannot be fully implemented. Therefore, perception is considered the initial stage of cognition in psychological science and is the main subject of many classical and modern studies.